2018
DOI: 10.1080/02656736.2018.1462535
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation (RFA)-induced systemic tumor growth can be reduced by suppression of resultant heat shock proteins

Abstract: Hepatic RF heating parameters alter periablational HSP70, which can influence and stimulate distant tumor growth. Modulation of RF heating parameters alone or in combination with adjuvant HSP inhibition can reduce unwanted, off-target systemic tumorigenic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…Heat shock protein expression was mainly observed in the periablational rim, as expected, where the temperature was in the scope of nonlethal thermal injuries. These results were consistent with the research findings of Ahmed et al, which showed that hepatic radiofrequency ablation heating parameters alter periablational HSP, which can influence and stimulate distant tumor growth. Modulation of radiofrequency heating parameters alone or in combination with adjuvant HSP inhibition can reduce unwanted, off‐target systemic tumorigenic effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Heat shock protein expression was mainly observed in the periablational rim, as expected, where the temperature was in the scope of nonlethal thermal injuries. These results were consistent with the research findings of Ahmed et al, which showed that hepatic radiofrequency ablation heating parameters alter periablational HSP, which can influence and stimulate distant tumor growth. Modulation of radiofrequency heating parameters alone or in combination with adjuvant HSP inhibition can reduce unwanted, off‐target systemic tumorigenic effects.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, this study combined an HSP90 inhibitor with MWA to determine the effect on tumor growth and the end point survival time in mice, and the results showed that combination treatment could reduce the tumor growth rate and prolong the end point survival time. These findings were closely related to the increase in the tumor necrosis range and immunohistochemical staining results observed in previous studies More importantly, although MWA prolonged the tumor growth time and terminal survival time compared to ganetespib, ganetespib alone showed greater survival benefits than the no‐treatment group, indicating that tumors were independently susceptible to ganetespib …”
Section: Discussionsupporting
confidence: 82%
“…7 Schematic diagram shows that collagen I initiates ERK signaling to accelerate the aggressive progression of residual HCC cells after sublethal RFA, which could be reversed by sorafenib. More factors implicated in post-inflammation reaction after RFA promote tumor progression of residual HCC, which has been reported by the other authors [ 14 , 15 , 49 , 50 ] …”
Section: Discussionsupporting
confidence: 64%
“…This study has several limitations. First, besides collagen I, we could not exclude the other factors in post-inflammation reaction after RFA that influence tumor progression of residual HCC [ 14 , 15 , 49 , 50 ], such as RFA-induced tumor-specific T-cell reaction, a Th1 cytokine pattern after RFA, heat shock proteins, periablational cellular infiltration. Second, we did not identify the source of collagen I.…”
Section: Discussionmentioning
confidence: 99%
“…35 Nonetheless modulation of RF heating parameters alone or in combination with adjuvant heat-shock proteins inhibition, STAT3 inhibition, or simple cyclooxygenase-2 selective non-steroidal antiinflammatory drugs can mitigate or reduce unwanted, off-target systemic tumorigenic effects. 36 Nevertheless, there may be a precarious and poorly understood balance between partial ablation or embolization inducing a tumorigenic response vs. an immune regression. Tipping this balance via pharmacomodulation may more fully recognize the preclinical promise and augmentation of HCC immunomodulation combined with local and regional image guided tools.…”
Section: B Amentioning
confidence: 99%